EKSPANSI GRAB KE INDONESIA TAHUN 2015-2018 - Lugi Dola Algina; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Grab is a technology company from Malaysia based in Singapore that provides public transportation service applications, in practice Grab operates in more than one country in order to expand its company network or carry out its expansion practices. Grab has been expanding in Indonesia since 2014 by considering its factors and strategies in expanding in Indonesia. This research is to find factores for grab to expand its therefore busines. To answer the question this research use qualitative research uses primary and secondary data collection methods. The level of analysis used in this study is the level of individual group analysis. This study asks what are the considerations of Grab in expanding to Indonesia. Multinational corporation theory is used by researchers to analyze data and obtain research results. Based on the research results obtained, it can be seen that there are 2 factors that Grab considers to expand to Indonesia, namely internal and external factors. In Multinational Corporation theory, the expansion carried out by a company is influenced by external and internal factors. Internal factors or push factors from Grab are Grab's ability to expand, then external factors or Pulling Factors, Grab's external factor in considering its expansion is the condition or potential of Indonesia. Keywords : Expansion, Grab, , online transportation ,MNC, Indonesia